2017
DOI: 10.1016/j.aorn.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Operation Clean Air: Implementing a Surgical Smoke Evacuation Program

Abstract: Surgical smoke is a hazardous byproduct of any surgery involving a laser or an electrosurgical unit. Although research and professional organizations identified surgical smoke as harmful many years ago, this byproduct continues to be a safety hazard in the OR. An interdisciplinary team at a large academic medical center sought to address the exposure of patients and perioperative team members to surgical smoke. The team used the nursing process to resolve the lack of smoke-evacuator equipment and surgical smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…In some places, this requires a rethinking of the interprofessional distribution of tasks. An American intervention study showed that if assistance staff is actively involved in risk assessment processes, personnel receive appropriate training and, in addition, an audit system for monitoring equipment usage is implemented and occupational health and safety can be protected [27,57]. A key component of the award-winning program was an interdisciplinary implementation team with facility coordinators who performed a gap analysis, coordinated between departments, identified champions, developed communication plans to address identified concerns, encouraged team involvement, and educated staff members about smoke-free working procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In some places, this requires a rethinking of the interprofessional distribution of tasks. An American intervention study showed that if assistance staff is actively involved in risk assessment processes, personnel receive appropriate training and, in addition, an audit system for monitoring equipment usage is implemented and occupational health and safety can be protected [27,57]. A key component of the award-winning program was an interdisciplinary implementation team with facility coordinators who performed a gap analysis, coordinated between departments, identified champions, developed communication plans to address identified concerns, encouraged team involvement, and educated staff members about smoke-free working procedures.…”
Section: Discussionmentioning
confidence: 99%
“… smoke evacuation will be used for all smoke‐producing procedures, the RN circulator is to assess each procedure that could generate plume and provide an evacuation method to remove smoke from the OR, and surgical smoke will be removed using a smoke evacuation system during open and laparoscopic procedures . (p507) …”
Section: Strategies For Successmentioning
confidence: 99%
“…Additionally, the team audited smoke evacuation practices during all procedures occurring in every OR during the eight‐hour workday, performed onsite education, and worked with perioperative team members to resolve problems. This team won the gold level Go Clear Award and will continue to maintain the program to uphold the safety and health of their patients and perioperative teams …”
Section: Strategies For Successmentioning
confidence: 99%
See 2 more Smart Citations